2021
DOI: 10.12659/msm.933450
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Maxillary Odontometrics for Sex Estimation Based on a 3-Dimensional Digital Method

Abstract: Background In the field of forensic medicine, sex estimation is a critical step in personal identification. Teeth are the hardest tissue and have high temperature resistance and corrosion resistance. In cases such as an airplane crash or the corpse of an unknown person, teeth often play a crucial role in identification. This study applied 3-dimensional technology to obtain odontometrics of permanent maxillary teeth and to examine the sexual dimorphism, finding suitable discriminant indicators to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
2
1
1
Order By: Relevance
“…Gupta et al [30] reported a higher percentage of gender dimorphism with respect to maxillary ICD and found that the right canine was more dimorphic compared to the left canine. Liu et al (2021), in a study on the Chinese population, revealed a slightly higher percentage (4.26%) of gender dimorphism for MD width of the left canine compared to the right canine (4.18%) [24]. In contrast to the present findings, a previous study on the Saudi Arabian population found a lower magnitude of gender dimorphism for maxillary canines [16].…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Gupta et al [30] reported a higher percentage of gender dimorphism with respect to maxillary ICD and found that the right canine was more dimorphic compared to the left canine. Liu et al (2021), in a study on the Chinese population, revealed a slightly higher percentage (4.26%) of gender dimorphism for MD width of the left canine compared to the right canine (4.18%) [24]. In contrast to the present findings, a previous study on the Saudi Arabian population found a lower magnitude of gender dimorphism for maxillary canines [16].…”
Section: Discussioncontrasting
confidence: 95%
“…In the present study, it was observed that the males had a tendency to have statistically significant higher mean values of ICD compared to the female counterparts (p < 0.001). This finding was consistent with those of other authors [16,24,30]. However, Shetty et al [32] and Alanazi et al [33], in their studies, reported no statistically significant differences in the mean maxillary ICD between males and females.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations